Machinery/service system Scheduled Replacement time determination: A combine Weighted Aggregated Sum Product Assessment, Additive Ratio Assessment and Age Replacement Model approach - Emovon, Ikuobase; Mgbemena, Chinedum (International Journal of Integrated Engineering, 2018)
The productivity of manufacturing/service industries greatly depend on the safety and reliability of the machinery/service system use for production/service delivery. The safety and reliability of the system can only be guaranteed through efficient maintenance. Scheduled replacement is an integral element of maintenance strategies. The major challenge of the maintenance policy is the determination of the optimum interval for carrying out replacement of equipment item of machinery/service system. A number of approaches have been applied in the literature in addressing this problem but these techniques have one limitation or another. In this paper, an MCDM approaches which avoid these limitations is proposed. The proposed Multi-Criteria Decision Making (MCDM) techniques combined weighted Aggregated Sum Product Assessment (WASPAS) and Additive Ratio Assessment (ARAS) with Age Replacement Model (ARM) for the determination optimum scheduled replacement time interval. The ARM for cost, reliability and downtime are aggregated using WASPAS and ARAS methods in order to rank alternative time intervals. The WASPAS and ARAS methods outputs are compared with another well-known technique in literature. To demonstrate the applicability of the proposed approaches a numerical example was applied. The result of the analysis revealed that, WASPAS and ARAS produces similar ranking for alternatives when compared with that of TOPSIS technique in the literature which is more computationally intensive, thereby validating the suitability of the proposed approaches.